Cognitive flexibility is associated with the age of onset and duration among patients with type 1 diabetes - Ding Mojun; Yuan Dongling; He Jing; Zou Wenjing; Li Xia; Li Chuting; Zhu Xiongzhao (Scientific Reports)
Abstract Cognitive impairment is a recognized risk in patients with type 1 diabetes, yet its contributing factors and overall impact remain insufficiently understood. This study aimed to explore the relationships between specific cognitive functions—namely memory, attention, and cognitive flexibility—and clinical characteristics, including age of onset and diabetes duration, as well as glycemic factors, such as glycemic control and extreme glycemic events, in a cohort of 331 patients with type 1 diabetes. Cognitive performance was assessed using the Wechsler Memory Scale, Wisconsin Card Sorting Test, and the Sustained Attention to Response Task. Network analysis revealed that age of onset and diabetes duration were central nodes in the network, strongly influencing cognitive flexibility. Additionally, age of onset was associated with a history of severe hypoglycemia, while diabetes duration was linked to visual memory decline. Significant differences were observed between the network structures of the adult-onset and childhood-onset groups, with the childhood-onset group showing greater interconnectedness. These findings emphasize the critical impact of age of onset and disease duration on cognitive outcomes in type 1 diabetes. Longitudinal studies are needed to further understand these relationships and guide targeted interventions to preserve cognitive function.